CDIO for introduction in civil engineering subject / Siti Rahimah Rosseli - Rosseli, Siti Rahimah (Unit Penerbitan FKAPP, 2022)
Conceive - Design - Implement - Operate, or CDIO, has been essential in creating a foundation for outcome-based assessment that is inherently accessible for most engineering subjects. Students are excited because they will graduate with a distinctive range of interpersonal, personal, and system-building experiences that will enable them to flourish in actual engineering teams and create new systems or products. CDIO is advantageous not only to students, but also to lecturers, who can devise interactive activities in the CDIO workspace. In addition, CDIO produces players with the specific knowledge, skills, and experience that the industry requires, aims to enrich CDIO as a cutting-edge educational environment for the next generation of talented leaders. And with that, to provide an enjoyable and competitive CDIO learning process and to address all the mentioned future benefits, a successful event was held. The CDIO competition for Introduction of Civil Engineering (ECM157) subject was conducted on 27th January 2023, at UiTM Pulau Pinang Branch and had been organized by several lecturers who taught ECM157 during the October 2022 - February 2023 semester. Part 1 students from Diploma in Civil Engineering (CEEC110) programme, 95 in total, participated in this big event. Students were required to work in groups of four to construct a model of a high-rise structure out of recyclable materials, including paperboard, plastic, cans, and glass. Before constructing the model, students must identify the problem with conventional high-rise buildings, engaged in a brainstorming session to generate plausible design alternatives, and select the best design based on a variety of factors. The building concept must met the requirements of the design idea, aesthetics, sustainability in the use of materials and construction, and advanced technology. Students were also required to present their projects, which were evaluated by a panel of qualified judges based on the building model and presentation skills. As Head of Programme for EC110/CEEC110, Encik Mohd Zaini Endut was invited to officiate the closing ceremony and present prizes to the winning teams and best presenters. It is anticipated that this fruitful event will continue in the future to foster CDIO in CEEC110 programme, as it has achieved its goals.